Some Coagulation Parameters, Fibrinogen, Protein C and Antithrombin III among Pregnant Women Visiting the Antenatal Clinic in University of Calabar - Adaku O. Okoli Dorathy C. Okpokam Mbang Ada-Kooffreh Euphoria C. Akwiwu Atim Udo (Sokoto Journal of Medical Laboratory Science)
No abstract